Establishment and Evaluation of a One‐Step Microplate Chemiluminescence Immunoassay to Detect IgG Antibody Against Treponema Pallidum. Issue 6 (2nd October 2014) - Liu, Lijuan; Xie, Yuling; Dai, Zhenxian; Zhuo, Chuanshang; Wu, Yushui
Abstract : Background: The serological detection of specific antibodies against Treponema pallidum is of particular importance in the diagnosis of syphilis. The chemiluminescence immunoassay (CLIA) has been widely used for clinical diagnosis because they remit no radical waste products, cause no enzyme precipitation, and exhibit an excellent sensitivity. Methods: A one‐step CLIA was established to detect T. pallidum IgG antibody based on microplate coated with a mixture of recombinant T. pallidum antigens TpN15, TpN17, and TpN47. The Chinese national reference substances standard panel for T. pallidum diagnosis was applied to test the accuracy, stability, interference, and cross‐reactivity of the established CLIA. The validation of efficacy for clinical application was performed by comparing the established method with the marketed T. pallidum particle agglutination (TPPA) kit and the Abbott ARCHITEC Auto System. Results: The established method met the requirement of the Chinese national reference substances standard for T. pallidum diagnosis. When compared with TPPA ( n = 1, 052), the specificity, sensitivity, and overall concordance were 99.7%, 99.0%, and 98.8% respectively, showing a great agreement with a kappa value of 0.81. When compared with the Abbott ARCHITEC Auto System ( n = 352), the results showed that the specificity, sensitivity, and overall concordance were 98.6.0%, 96.6% and 98.6% respectively, and a high‐degree agreement was observed (kappa value = 0.95). Conclusion: The established rapid, specific, sensitive, and stable microplate CLIA method to detect IgG antibody against T pallidum will provide an efficient alternative to the treponemal tests and wide application in clinical laboratory.